Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah pada Bank Perkreditan Rakyat Kerta Raharja Kantor Pusat Soreang - Reza Miftah Pebrianto; Rita Zulbetti (Ekonomis: Journal of Economics and Business, 2022)
This study aims to analyze the impact of service quality on customer loyalty at Bank Perkreditan Rakyat (BPR) Kerta Raharja Soreang Head Office. The methods used in this research are the descriptive research method and the simple linear regression analysis method with questionnaire distribution technique. The determination of respondents in this study was made using Slovin’s formula, so that the respondents used could be as many as 100 people. From the results of this study, it is concluded that the impact of service quality on customer loyalty at Bank Perkreditan Rakyat Soreang Head Office has a positive significance, meaning that both variables have a strong significance. Simultaneously, the impact of service quality on customer loyalty at Bank Perkreditan Rakyat Soreang Head Office also has a strong significance, meaning that the better the service quality at Bank Perkreditan Rakyat Soreang Head Office, the customer loyalty will also increase.